Correlations Between Real Interest Rates and Output in a Dynamic International Model : Evidence from G-7 Countries - Zaman, Jahanara (IMF Working Papers; Working Paper ;, 1998)
This paper examines the extent to which a dynamic international general equilibrium model can account for observed movements in real interest rates and interest rate differentials. Using data for Group of Seven, the study finds that measured real interest rates are countercyclical in a single country and that the contemporaneous cross-correlations between international real interest differentials and output growth spreads are negative. Predictions of the baseline model are, however, inconsistent with the data. Extending the benchmark model to include habit persistence in consumption improves the match between theory and data.